Peran Komite Audit dalam Hubungan antara Metode Nilai Wajar dengan Biaya Audit: Studi Kasus Di ASEAN - Ghofananda, Viva Nuralifiya; Mita, Aria Farah (APSSAI, 2023)
This research discusses the impact of the fair value method on fixed assets, audit fees, and audit committees in ASEAN. The samples of the research are 277 manufacturing companies listed in the Indonesia Stock Exchange, Malaysia Stock Exchange, Singapore Stock Exchange, Philippine Stock Exchange, and Thailand Stock Exchange from 2014 to 2016. The results of the study found that companies that use the fair value method through a revaluation model to measure their fixed assets have higher audit fees than those that use the historical cost method. In addition, there is a moderation effect of audit committee competencies on the relation of fair value method to audit fee. The findings prove that the accounting and financial competencies of the audit committees reduce audit fees imposed on companies using the fair value method for fixed assets.